SELF-ASSESSMENT OF STUDENTS’ AMBITION - Barsukova, Oksana (Journal of process management and new technologies, 2017)
The article presents the results of empirical study of the self-assessment of ambition by university students. Most students consider themselves as ambitious persons and assess their ambition as moderate.